Through the ivory gate: studies in psychology and history - Ireland, William W. (G.P. Putnam's, 1889)
Emanuel Swedenborg.--William Blake.--The insanity of King Louis II, of Bavaria.--Charles J. Guiteau.--Louis Riel.--Gabriel Malagrida.--Theodore of Abyssinia.--Thebaw, king of Burma.